2018
DOI: 10.1152/ajpendo.00315.2017
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of parasympathetic muscarinic augmentation of insulin secretion to olanzapine-induced hyperinsulinemia

Abstract: Atypical antipsychotic drugs have been associated with the development of obesity and diabetes. In particular, olanzapine can induce peripheral insulin resistance and compensatory hyperinsulinemia independent of weight gain or psychiatric disease. To determine if this compensatory increase in insulin is mediated by parasympathetic muscarinic stimulation, we randomized 15 healthy subjects 2:1 to receive double-blind olanzapine or placebo for 9 days under diet- and activity-controlled inpatient conditions. Befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Olanzapine-induced hyperinsulinemia has been observed previously in studies of patients with schizophrenia [32,33] and healthy volunteers [30,34]. The findings of this study are consistent with reports that hyperinsulinemia results from increases in insulin secretion from the pancreas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Olanzapine-induced hyperinsulinemia has been observed previously in studies of patients with schizophrenia [32,33] and healthy volunteers [30,34]. The findings of this study are consistent with reports that hyperinsulinemia results from increases in insulin secretion from the pancreas.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple mechanisms may account for olanzapine-mediated increases in insulin secretion, including alterations in neuronal modulation of the pancreas and even direct effects of dopamine receptor antagonism on pancreatic β-cells [35][36][37]. One study of intravenous glucose tolerance tests in healthy volunteers treated with olanzapine demonstrated an essential role of sympathetic input via muscarinic receptors in mediating the olanzapine-induced hyperinsulinemic response to glucose challenge [34]. More recently, it has been reported that pancreatic αand β-cells not only express D2-like dopamine receptors but also are capable of local catecholamine synthesis [36].…”
Section: Discussionmentioning
confidence: 99%
“…On this aspect, the effect of AAPs is controversial because besides blocking muscarinic receptors, clozapine and olanzapine seem to increase the parasympathetic cholinergic output that probably leads to a rebound on the vagal system with compensatory stimulation of the β-cells [ 63 , 89 ]. In a study, olanzapine administrated for 9 days increased insulin and C peptide secretion that was reduced by atropine treatment, thus confirming the role of muscarinic receptor stimulation [ 90 ]. Clozapine and olanzapine-induced insulin dysregulation may also be partly due to blockade of hypothalamic M 3 receptors [ 91 ].…”
Section: Effects Of Aaps On Hypothalamus and Peripheral Tissuesmentioning
confidence: 92%
“…59 Finally, OLZ/SAM consistently mitigated olanzapine-associated weight gain across a range of species/populations (eg, rodents, nonhuman primates, healthy individuals, and patients with schizophrenia), 60,62,71 and antipsychotic-associated weight gain and metabolic dysregulation occur independently of disease. [102][103][104]…”
Section: Other Populationsmentioning
confidence: 99%